2013
DOI: 10.1159/000354370
|View full text |Cite
|
Sign up to set email alerts
|

Rate of Conversion from Prodromal Alzheimer's Disease to Alzheimer's Dementia: A Systematic Review of the Literature

Abstract: Background: The purpose of this study was to summarize published estimates for conversion from mild cognitive impairment or amnestic mild cognitive impairment to Alzheimer's dementia. We carried out a systematic review of English language publications to identify cohort studies published since January 2006 that reported the risk or rate of conversion. Summary: Thirty-two cohort studies were identified, of which 14 reported annualized conversion rates (ACRs). Conversions over 1 year ranged from 10.2 to 33.6% (5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
216
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 314 publications
(249 citation statements)
references
References 62 publications
(176 reference statements)
6
216
1
3
Order By: Relevance
“…31,32 Anywhere from 32 to 38% of people with MCI progress to AD in 5 years or longer. 32,33 Annual rates of progression have been estimated to be 10 to 15%. 912 These findings have naturally generated an interest in using disease modifying agents to not only preserve cognitive function in MCI individuals but also slow their conversion to dementia.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 Anywhere from 32 to 38% of people with MCI progress to AD in 5 years or longer. 32,33 Annual rates of progression have been estimated to be 10 to 15%. 912 These findings have naturally generated an interest in using disease modifying agents to not only preserve cognitive function in MCI individuals but also slow their conversion to dementia.…”
Section: Discussionmentioning
confidence: 99%
“…This recommendation was formulated based on an existing systematic review which found that, in a clinic setting, the annual conversion rate of mild cognitive impairment to Alzheimer disease was close to 10%. 12 At the time of diagnosis of dementia, and at regular intervals subsequently, assessment should be made for medical comorbidities and key psychiatric features associated with dementia, including depression, to ensure optimal management of coexisting conditions.…”
Section: Changes In Managementmentioning
confidence: 99%
“…MCI is characterized by cognitive decline that exceeds the expected decline from aging, but does not greatly impact independent functioning [112]. Critically, patients with MCI are more likely to develop AD than cognitively normal adults [113-115], with higher conversion rates in amnestic MCI (aMCI) than nonamnestic MCI (naMCI) [113,116; also see 117 for a discussion of conversion rates]. Furthermore, MCI has been viewed as a possible prodromal stage of AD [112-114], so any changes in eye movements that are potentially detectable in MCI, especially aMCI, are greatly important to AD research.…”
Section: Clinical Application Of Eye Movement Measurementsmentioning
confidence: 99%